Neuroprotective effects of trigonelline in eggplant on oxidative damage of PC12 cells and cognitive impairment in aging mice - Jiahui Feng; Weihua Liu; Danqi Feng; Bimal Chitrakar; Xueping Chen; Yaxin Sang; Xianghong Wang (Journal of Functional Foods, 2024)
Oxidative stress-induced neuronal damage is the main cause of neurodegenerative diseases, which is characterized by cognitive impairment. We selected a high-content natural alkaloid, trigonelline, from daily vegetables eggplants. The results showed that eggplants were rich in trigonelline. It has antioxidant and anticancer effects, but there is limited research on neurodegenerative diseases. An in vitro neuronal injury model was established using PC12 cells damaged by H2O2 to explore neuroprotective effect of trigonelline. An aging model was established in vivo by injecting D-galactose into mice for 6 weeks. Trigonelline have been found to improve cognitive impairment by improving brain-damage, enhancing antioxidant system activity in mice, regulating the activity of ChAT and AChE to maintain the balance of cholinergic system. The experimental results indicate that trigonelline has good neuroprotective effects, providing a reference for the development of functional foods made from eggplant and trigonelline, as well as prevention and treatment of neurodegenerative diseases.